The structuring of work in organizations - Cohen, Lisa E.; Burton, M. Diane; Lounsbury, Michael (Bingley, U.K. : Emerald, 2016)
Differences in management behavior across organizations are attributed to differences in priorities and objectives or differences in the style and preferences of the individuals involved. This volume challenges this image by attending to the extra-organizational and extra-individual forces that shape and constrain how work is structured in organizations. The authors focus their attention on work within and between organizations and emphasize the ways in which the jobs are defined, the power and autonomy they engender, the opportunities that are afforded, and the constraints that are imposed, are continuously contested not only at the individual level, but also at a more aggregate and collective level. This volume is the product of an interdisciplinary gathering of scholars convened with generous support of the Canadian Social Science and Humanities Research Council. It presents new theoretical and empirical papers that examine aspects of the changing nature of jobs and work in organizations from multiple perspectives and methodologies.
Introduction: bringing jobs back in: towards a new multi-level approach to the study of work and organizations / M. Diane Burton, Lisa Cohen, Michael Lounsbury -- Jobs as Gordian knots a new perspective linking individuals, tasks, organizations and institutions / Lisa Cohen -- Idiosyncratic jobs, organizational transformation, and career mobility / Anne Miner, Olubukunola (Bukky) Akinsanmi -- The ideology of silence at the Harvard Business School: structuring faculty's teaching tasks for moral relativism / Michel Anteby -- What do technicians mean when they talk about professionalism? an ethnography of speaking / Stephen Barley, Beth Bechky, Bonalyn Nelsen -- Compliance police or business partner? institutional complexity and occupational tensions in human resource management / Kurt Sandholtz, Tyler Burrows -- Structure at work: organizational forms and the division of labor in U.S. wineries / Heather Haveman, Anand Swaminathan, Eric Johnson -- It's not you, it's your job: network evolution within firms / Jennifer Kurkoski -- Help me do it on my own: how entrepreneurs manage autonomy and constraint within incubator organizations / Victor Seidel, Kelley Packalen, Siobhan O'Mahony -- Legal avoidance and the restructuring of work / Charlotte Alexander -- Externalization of work by corporate law firms: implications for careers and the profession / Christine Riordan, Paul Osterman -- Work as commons: internal labor markets, blended workforces and management / Arnaldo Camuffo, Federica De Stefano -- From adapting practices to inhabiting ideas: how managers restructure work across organizations / Ruthanne Huising.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Organizational Behavior; Organizational theory & behaviour; Corporate culture; Personnel management